The Curcumin Analog GO-Y030 Controls the Generation and Stability of Regulatory T Cells - MaruYama, Takashi; Kobayashi, Shuhei; Nakatsukasa, Hiroko; Moritoki, Yuki; Taguchi, Daiki; Sunagawa, Yoichi; Morimoto, Tatsuya; Asao, Atsuko; Jin, Wenwen; Owada, Yuji; Ishii, Naoto; Iwabuchi, Yoshiharu; et al. (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) play a crucial role in preventing antitumor immune responses in cancer tissues. Cancer tissues produce large amounts of transforming growth factor beta (TGF-β), which promotes the generation of Foxp3+ Tregs from naïve CD4+ T cells in the local tumor microenvironment. TGF-β activates nuclear factor kappa B (NF-κB)/p300 and SMAD signaling, which increases the number of acetylated histones at the Foxp3 locus and induces Foxp3 gene expression. TGF-β also helps stabilize Foxp3 expression. The curcumin analog and antitumor agent, GO-Y030, prevented the TGF-β-induced generation of Tregs by preventing p300 from accelerating NF-κB-induced Foxp3 expression. Moreover, the addition of GO-Y030 resulted in a significant reduction in the number of acetylated histones at the Foxp3 promoter and at the conserved noncoding sequence 1 regions that are generated in response to TGF-β. In vivo tumor models demonstrated that GO-Y030-treatment prevented tumor growth and reduced the Foxp3+ Tregs population in tumor-infiltrating lymphocytes. Therefore, GO-Y030 exerts a potent anticancer effect by controlling Treg generation and stability.